Effect of the Proposed Outlets on the Hydrodynamic Behavior and Water Quality of the South-West Part of the Al Hammar Marsh (Journal of Engineering, 2023)
The current study aims to find a new plan to manage the water quality of the western part of the Hammar Marsh to reduce the salts that cause problems for the marshes and preserve their environmental life by isolating the southwestern part of the Hammar Marsh by closing the outlet under the railway embankment. The outlet is discharging saline water to the east-western part of Al Hammar Marsh. After isolating the southwestern part of the marsh, a new outlet is proposed. The impact of the flow hydrodynamics on improving the water quality was simulated using the SMS model. The hydrodynamics and water quality simulation models for the marsh are : a hydrodynamic model and average depth (SMS RMA2) and a two-dimensional water quality model (SMS RM4). The Civil3D was used to determine the area elevation curve for the marsh, while the shape file for the study area was prepared using the Arc-GIS model. The first model is used to simulate the flow conditions in the marsh (water depth and velocity vectors), while the second model is used to simulate the salinity of the water (Total Dissolved Solids (TDS)). For calibration and verification the models, water samples were taken from ten selected locations within the marsh. The measurements were conducted on 1st January and on 2nd February 2022. The simulation results were validated with the field measurement, and the discrepancy between the simulated and measured water depth was found to be 11%. Many scenarios are based on the proposed recommended outlet that considerably reduces TDS concentration in the Al Hammar marsh. Three scenarios were run on the proposed outlet to maintain a submerged area of 88 km2, and to compare the three scenarios, ten points were selected in different locations, where the average TDS ratio for the first scenario was 7528 mg/l, the second scenario was 6982 mg/l and for the third scenario was 8069 mg/l. Results showed that the proposed outlet would improve the hydrodynamics of the flow and reduce the TDS concentration by 10% in addition to controlling the contamination of east western part of the marsh